Six mitophagy-related hub genes as peripheral blood biomarkers of Alzheimer’s disease and their immune cell infiltration correlation - Zhao, Kun; Wu, Yinyan; Zhao, Dongliang; Zhang, Hui; Lin, Jianyang; Wang, Yuanwei (Frontiers in Neuroscience, 2023)
Background: Alzheimer’s disease (AD) is a neurodegenerative disorder with progressive symptoms which seriously endanger human health worldwide. However, it lacks ideal diagnosis and treatment. Therefore, molecular biomarkers show potential prospects. The purpose of this study was to investigate available promising diagnostic biomarkers of peripheral blood in AD. Method: Utilizing three microarray datasets we systematically analyzed expression difference and predictive value of mitophagy related genes (MRHGs) in peripheral blood mononuclear cells (PBMCs) of AD, and identified potential diagnostic biomarkers. Subsequently protein-protein interaction (PPI) network was constructed to identify hub genes and functional enrichment analysis was also performed. Then, the AD subtypes with significant differences were determined by using consistent clustering analysis. Finally, infiltration patterns of immune cells in AD subtypes and the relationship between MRHGs and immune cells were investigated by two algorithms, CIBERSORT and Single-Sample Gene Set Enrichment Analysis (ssGSEA). Result: Our study identified 53 AD related MRDEGs and six mitophagy related hub genes (MRHGs), which may be potential biomarkers for diagnosing AD. A functional analysis revealed that six MRHGs significantly affected biologically relevant functions and signaling pathways such as IL4 signaling pathway, RUNX3 regulating Notch signaling, IL1 and megakaryocytes in obesity, and Overview of Leukocyteintrinsic Hippo Pathway Functions. Further, for all AD samples, the results of CIBERSORT and ssGSEA algorithms used to analyze the immune infiltration abundance of immune cells in the two disease subtypes showed that they were mainly related to immune cells such as Mast cells activated, T cells regulatory, M0 Macrophages, and Neutrophils, and there is a significant correlation between the certain MRHGs and immune cells. Conclusion: As a result of these findings, it appears that MRHGs may contribute to the apprehending of AD's development and prognosis. The six MRHGs could be used as valuable diagnostic biomarkers for further research of AD. There is a possibility that this study can provide new promising diagnostic and therapeutic targets for AD in peripheral blood.